The Hidden Anxiety Trigger: How Caffeine Impacts Mental Health (Homoeopathy for All, 2024)
Caffeine, common in coffee and tea,  can boost alertness but also trigger  anxiety, especially in sensitive  individuals. This paper explores how  caffeine affects the nervous system,  potentially worsening anxiety  symptoms, and discusses strategies  like moderation and mindful  consumption to manage these effects  and support mental health.
Keywords: Anxiety disorder; Caffeine; Mental health